DNA methylation of selected tumor suppressor genes in endometrial hyperplasia - Dvořák, Ondřej; Ndukwe, Munachiso Onyedikachi; Slavíčková, Marcela; Laco, Jan; Špaček, Jiří (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
AIMS: To investigate DNA methylation of specific gene promoters in endometrial hyperplasia compared to normal endometrial tissue. MATERIALS AND METHODS: To search for epigenetic events, methylation-specific multiplex ligation-dependent probe amplification was employed to compare the methylation status of 64 tissue samples with atypical endometrial hyperplasia, 60 tissue samples with endometrial hyperplasia without atypia, and 40 control tissue samples with normal endometrium. RESULTS: Differences in DNA methylation among the groups were found in PTEN, CDH13, and MSH6 promoters (PTEN: atypical hyperplasia 32%, benign hyperplasia 6.8%, normal endometrium 10%; P=0.004; CDH13: atypical hyperplasia, 50%; benign hyperplasia, 43%; normal endometrium 8.1%; P=0.003; MSH6 atypical hyperplasia 84%, benign hyperplasia, 62%; normal endometrium, 52%; P=0.008.) Higher rates of CDH13 promoter methylation were identified in the groups with both forms of endometrial hyperplasia when compared to the control group (atypical hyperplasia, P=0.003, benign hyperplasia, P=0.0002). A higher rate of DNA methylation of the PTEN and MSH6 promoters was observed in samples with atypical endometrial hyperplasia than in samples with benign endometrial hyperplasia (PTEN: P=0.02; MSH6: P=0.01) and samples with normal endometrial tissue (PTEN, P=0.04; MSH6, P=0.006). CONCLUSION: DNA methylation of CDH13, PTEN, and MSH6 appear to be involved in the development of endometrial hyperplasia.
Keywords: Endometrial Hyperplasia; Genes, Tumor Suppressor; tumor supresorové geny; Female; nádory endometria; hyperplazie; DNA Methylation; Endometrial Neoplasms; metylace DNA; Humans; ženské pohlaví; DNA-Binding Proteins; hyperplazie endometria; lidé; DNA vazebné proteiny; Hyperplasia